I mødet mellem arbejde og familie : Om forholdet mellem arbejdsliv og familieliv hos højtuddannede kvinder - Humle,Didde Maria (2005)
The aim of this report is to obtain a greater understanding of the relationship between work and family for highly educated employed women with children and to elucidate which factors make this relationship more or less conflict-ridden and stressful. The qualitative empirical investigation consists of in-depth interviews with eight women combined with a questionnaire to measure their general well-being. There is no one-sided conclusion, but interestingly many of the respondents find themselves able to live up to the demands of both work and family and the results of the questionnaire show that their general well-being is good. However many of the respondents have occasionally experienced a feeling of inadequacy in respect to both family and work which hold a threat to their well-being. Some factors seem particularly central to the relationship between work and family: Working culture, work hours, responsibility, ambitions, the attitudes of management and colleagues, gender related differences, discrepancies between expectations and actual behaviour.
Keywords: akademiker; kvinnor; familj; arbete; Gender studies; Genusvetenskap; Psychology; Psykologi